(untitled) (Al-Academy, 2026)
Accelerated technological progress has led to excessive energy consumption and the depletion of current resources without guaranteeing the rights of future generations, in addition to the state of current cities that suffer from all kinds of pollution and high air temperatures, which necessitated the need to truly think about adopting new methods in the interior design of contemporary buildings for the purpose of preserving them and achieving development. Sustainable, so simple or minimalism is one of the methods that has been commonly used recently in design, as this method relies on design mechanisms aimed at reducing the need to use furniture and some other elements in the interior space, to provide more space and get rid of clutter, and on the other hand The simple design of homes contributes to conserving energy and reducing environmental pollution, and thus the research problem was represented in the following: “What is minimalist or simple design and what is its role in achieving a sustainable indoor environment?” The study aimed to reveal the positive features of the outcomes of simple minimalist design and its role in formulating the compositional and visual elements to achieve environmentally sustainable interior spaces. In order to implement the research objective, the researcher conducted an extensive study that included three chapters, the first of which dealt with the research problem, its importance, and its purpose, as well as setting boundaries and defining the terms included. The second chapter contained the theoretical framework, which in turn included three sections, the first of which took into account the simple design and its formal characteristics. Then the second section dealt with sustainability and its basic principles, while the third section dealt with simple sustainable design, its methods and applications, and then came up with a set of conclusions and presented several recommendations.